Epidemiology, Clinical Manifestations, and Outcomes of Streptococcus suis Infection in Humans - Vu Thi Lan Huong; Ngo Ha; Nguyen Tien Huy; Peter Horby; Ho Dang Trung Nghia; Vu Dinh Thiem; Xiaotong Zhu; Ngo Thi Hoa; Tran Tinh Hien; Javier Zamora; Constance Schultsz; Heiman Frank Louis Wertheim; et al. (Emerging Infectious Diseases, 2014)
Streptococcus suis, a bacterium that affects pigs, is a neglected pathogen that causes systemic disease in humans. We conducted a systematic review and meta-analysis to summarize global estimates of the epidemiology, clinical characteristics, and outcomes of this zoonosis. We searched main literature databases for all studies through December 2012 using the search term “streptococcus suis.” The prevalence of S. suis infection is highest in Asia; the primary risk factors are occupational exposure and eating of contaminated food. The pooled proportions of case-patients with pig-related occupations and history of eating high-risk food were 38.1% and 37.3%, respectively. The main clinical syndrome was meningitis (pooled rate 68.0%), followed by sepsis, arthritis, endocarditis, and endophthalmitis. The pooled case-fatality rate was 12.8%. Sequelae included hearing loss (39.1%) and vestibular dysfunction (22.7%). Our analysis identified gaps in the literature, particularly in assessing risk factors and sequelae of this infection.